LOCAL WISDOM AS SOCIAL COHESION IN ESTABLISHING INTER-RELIGIOUS LIFE IN DONGGO, DISTRICT OF BIMA (Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
Cultural values recently have been degraded, and have begun to be forgotten by society due to the times. Yet, apart from that, the certain cultures are very suitable to be developed and preserved. One of the benefits is to realize life together in the frame of religion plurality, realizing social harmonization is a necessity that must be lived by every individual or society. There are several villages in Bima, especially in Donggo that live in multicultural religion frame, one of which is in Mbawa, Tolo Nggeru and Palama Village. The religions that are believed by the community are Islam, Catholics and Protestant. In sulking inter-religion life, there must be a standard of togetherness values so as not bring up polemics in life. Therefore, we can see the social cohesion built by the inter-religious community in the region makes local wisdom a medium in sulking the values of religious moderation. In analysing this research, we used qualitative research with a phenomenological approach, and the process of collecting data through observation, documentation and interviews. Indeed, local wisdom made by community can be used by the community as a value of togetherness in the life inter-religious people. So the local wisdom used is the tradition of “tekara ne’e” and ”Mbolo weki”and open communication. Really helps the community in sulking the life of inter-religious society.